Meninjau Praktik Kebijakan Tanam Paksa di Hindia Belanda 1830-1870 - Aprilia, Alfa Tirza; Irawan, Hendi; Budi, Yusuf (Estoria: Journal of Social Science and Humanities, 2021)
This research discusses the practice of forced cultivation in the Dutch East Indies in the period 1830 to 1870. The method used in this research is the historicalmethod and its presentation in the form of a narrative description. The results ofthis study explain that the practice of forced cultivation in the Dutch East Indieshad a very large influence on the Netherlands and the people of the NetherlandsIndies. The system of forced cultivation changed the role of the colonialgovernment and native rulers, changed the social conditions of rural communitiesby giving birth to the concept of communal land and the introduction of the moneyeconomy system in the countryside. The forced cultivation system also succeededin filling the empty treasury of the Netherlands, but on the one hand it causedsuffering for the people of the Dutch East Indies. The famine caused byexploitation of land and human resources is a consequence of the implementationof the forced cultivation policy. The other side of the implementation of the forcedcultivation policy was the entry and introduction of export commodity crops to thepeople of the Dutch East Indies. Keyword: forced cultivation, colonial government, people, farmersAbstrak